2015
DOI: 10.1159/000441781
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status Is Related to Oxidative Stress But Not High-Sensitive C-Reactive Protein in Women with Pre-Eclampsia

Abstract: Background/Aims: Pre-eclampsia (PE) is associated with unfavorable metabolic profiles. Oxidative stress and inflammation have been increasingly postulated as major contributors to PE. Research suggests that vitamin D status is disturbed in women with PE. The aims of this study were to compare the serum levels of vitamin D and oxidative stress status in women with PE vs. women with normal pregnancies, and to evaluate the relationship between these 2 factors in women with PE. Methods: In this case-control study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…The results of current study correlates with what was found in (37) as there was no association between vitamin D deficiency and an active of protein C stimulation. Vitamin D affects the stimulation of T & B lymphocytes and regulates the immune system (12) .…”
Section: Concentration Of C-reactive Proteinsupporting
confidence: 91%
“…The results of current study correlates with what was found in (37) as there was no association between vitamin D deficiency and an active of protein C stimulation. Vitamin D affects the stimulation of T & B lymphocytes and regulates the immune system (12) .…”
Section: Concentration Of C-reactive Proteinsupporting
confidence: 91%
“…Similar to our data the findings of a trial showed that vitamin D supplementation had no effect on OS biomarkers among pregnant women with GDM [ 55 ]. However, there are some evidence that support a positive association between TAC and vitamin D status [ 41 , 65 ]. The findings of a systematic review of clinical trials among non-pregnant participants revealed that vitamin D only with doses of 100,000–200,000 IU/month could have beneficial effect on the OS parameters (decreases MDA levels and increases GSH and TAC levels) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In common with many other inflammatory diseases (145), Vitamin D 3 levels [usually measured as 25(OH)vitD or calcidiol] are often lower in PE (990994) [cf. Ref.…”
Section: Metabolomic Biomarkersmentioning
confidence: 99%